The longer-term fiscal challenges facing the European Union - Jeromin Zettelmeyer; Gregory Claeys; Zsolt M. Darvas; Lennard Welslau; Stauros Andrea Zenios (Bruegel, 2023)
The pandemic and subsequent price shocks triggered by Russia's invasion of Ukraine, have increased longer-term fiscal pressures in the European Union through higher debt, higher expected real interest rates and higher public investment needs. This Policy Brief makes some simple quantitative assessments of those effects and discusses policy implications, with the following results. First, long-term increases in primary fiscal balances required to offset higher debt and higher expected real interest rates are in the range of 0.5 percent to 1.5 percent of GDP for most EU countries. However, because of pre-existing differences in fiscal space, not all countries will need to undertake that adjustment, while some countries may need to adjust by substantially more. Among the 21 EU countries for which we have data to undertake this analysis, 14 will need to adjust by more than they were planning to do by 2025. Second, the required additional fiscal adjustment looks manageable, although it is substantial in some cases. To achieve medium-term debt-reducing primary balances, several EU countries will need to raise primary balances by more than 2 percent of GDP above their 2025 target, but no country will need additional fiscal adjustment of more than 3 percent of GDP. Third, market data suggests that the future path of real interest rates is very uncertain. Compared to the period immediately preceding the pandemic, longer-term expected real interest rates have increased by about 2 percentage points but remain low on average, at about 1 percent in real terms. Future developments depend on whether the structural factors that led to low interest rates in the first place persist or unwind. While interest rates might decline again, fiscal policymakers should not make plans that assume such a decline. Fourth, public spending needs for additional defence and climate spending run well above 1 percent of GDP per year. These needs do not appear to have been incorporated into current fiscal baselines, and hence will come on top of the adjustment described above. To ensure that fiscal adjustment does not defeat its purpose by slowing growth, it is essential that it is conducted gradually. In countries that require such adjustment, it should start as soon as cyclical conditions allow.
Keywords: 330